2012
DOI: 10.1097/ta.0b013e318265cb75
|View full text |Cite
|
Sign up to set email alerts
|

Placement of intracranial pressure monitors by non-neurosurgeons

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Yet, the current practice of skilled neurosurgeons being required for invasive skull procedures has been debated in a recent study by Barber et al 32 This study, consisting of patients within a single trauma center, revealed that the placement of ICP monitors may be performed safely by both neurosurgeons and non-neurosurgeons in a trauma center. 33 Given the high transfer rate to definitive care Level I or II trauma centers, as found in this present study, the Barber study results may not be generalized to all non-trauma center environments due to staffing differences at non-trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the current practice of skilled neurosurgeons being required for invasive skull procedures has been debated in a recent study by Barber et al 32 This study, consisting of patients within a single trauma center, revealed that the placement of ICP monitors may be performed safely by both neurosurgeons and non-neurosurgeons in a trauma center. 33 Given the high transfer rate to definitive care Level I or II trauma centers, as found in this present study, the Barber study results may not be generalized to all non-trauma center environments due to staffing differences at non-trauma centers.…”
Section: Discussionmentioning
confidence: 99%
“…The reference standard for diagnosing intracranial hypertension is the invasive measurement of ICP using ventricular drains or cerebral catheters and microsensors placed through a burr hole drilled in the skull [ 3 ]. However, invasive ICP measurement may not be available in certain situations, such as in underserved rural areas, in developing countries with limited resources or in settings outside the intensive care unit (ICU) and neurosurgical departments [ 4 ]. In several conditions, such as liver failure, preeclampsia, encephalitis, meningitis and stroke, the role of invasive ICP monitoring is not well established or the risk–benefit ratio remains unclear [ 5 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Barber et al 13 from Wichita, Kansas, demonstrated safe insertion by both neurosurgeons and nonneurosurgeons and proposed that this procedure be adopted as a core skill for trauma surgeons and surgical residents. Barber et al 13 from Wichita, Kansas, demonstrated safe insertion by both neurosurgeons and nonneurosurgeons and proposed that this procedure be adopted as a core skill for trauma surgeons and surgical residents.…”
Section: Discussionmentioning
confidence: 99%